2010
DOI: 10.1021/jp106818p
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ferromagnetism in Vacuum-Annealed CoO Nanospheres

Abstract: Single-crystalline CoO nanospheres with the size distribution between 40 and 250 nm were prepared by a solvothermal method. Magnetic measurements indicate that the vacuum-annealed samples show room temperature ferromagnetism except for the CoO nanospheres of 250 nm, which still exhibit paramagnetism after being postannealed in vacuum atmosphere (10−3 Pa) at 250 °C as others. The saturation magnetization of all postannealed samples monotonically increases with the decrease of nanosphere diameter. No other impur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 37 publications
7
39
0
Order By: Relevance
“…These results are in concordance with earlier studies in wurtzite‐CoO, which show a ferromagnetic response, even at room temperature . Note that the strong ferromagnetic‐like behavior can be tentatively explained by the presence of uncompensated spins arising from the existence of a rather large amount of oxygen vacancies (note the CoO 0.7 stoichiometry of the particles), with the FM signal being roughly proportional to the number of such vacancies . Concerning the dependence of the coercivity, H C , with temperature it can be observed that at low temperatures, there is an increase in H C , determined by the increase of the magnetic anisotropy related with the freezing of the surface disorder.…”
Section: Resultssupporting
confidence: 91%
“…These results are in concordance with earlier studies in wurtzite‐CoO, which show a ferromagnetic response, even at room temperature . Note that the strong ferromagnetic‐like behavior can be tentatively explained by the presence of uncompensated spins arising from the existence of a rather large amount of oxygen vacancies (note the CoO 0.7 stoichiometry of the particles), with the FM signal being roughly proportional to the number of such vacancies . Concerning the dependence of the coercivity, H C , with temperature it can be observed that at low temperatures, there is an increase in H C , determined by the increase of the magnetic anisotropy related with the freezing of the surface disorder.…”
Section: Resultssupporting
confidence: 91%
“…From all these TEM images, we conclude that shape-selective CoO NPs are formed at high yields by changing the concentration of reaction parameters. The peak positions matches with previous reports (Park et al 2004, Yang et al 2010, Lagunas et al 2008, Zhang et al 2002. Lagunas et al (Lagunas et al 2008) observed a broader XRD pattern in their study due to formation of very small CoO NPs.…”
Section: Resultssupporting
confidence: 89%
“…Several groups report synthesis of cobalt nanoparticles (Yin et al 1997, Zhang et al 2008, Ghosh et al 2005, Risbud et al 2005, Park et al 2004, Liu et al 2006, Verelst et al 1999, Jana et al 2004, Do et al 2005, Zhan et al 2003, Yang et al 2010. The magnetic properties of CoO NPs were also studied by several groups (Wdowik et al 2008, Dutta et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In nanostructured AFM materials10 pairing of the two mutually compensating ferromagnetic sublattices is broken due to surface rearrangement, which leads to the presence of “uncompensated” and often “frustrated” surface moments and the consequent magnetic reconstruction11. Several examples of weak ferromagnetism in nanoparticulate CoO121314 and Co 3 O 4 151617 materials have been reported in the literature based on these explanations, though the irregular shapes and the relatively wide size distributions of nanoparticles have made a detailed analysis of the origin of the observed ferromagnetic response very difficult. In contrast, nearly perfect antiferromagnetic CoO nanocrystals with octahedron shapes and different average sizes, as reported in Ref.…”
mentioning
confidence: 99%